Realizace hrubé vrchní stavby rodinného domu v Lanškrouně - Faltys, David (Vysoké učení technické v Brně. Fakulta stavební, 2016)
Předmětem bakalářské práce je řešení technologické etapy hrubé vrchní stavby rodinného domu v Lanškrounu. Práce obsahuje technickou zprávu, řešení širších dopravních vztahů, technologický předpisy pro zdění a hrubou konstrukci střechy, zařízení staveniště, časový plán, návrh strojní sestavy, kontrolní a zkušební plány a bilance zdrojů.

The subject of work is the solution of stage gross superstructure family house in Lanškroun. The work includes construction technology report, addressing broader transport relations, technological specification for gross masonry and for gross roof, construction site, inspection and test plan, design of mechanical assembly, control and test plans and evaluation source.
Execution of structural works of superstructural building in a family house in town of Lanškroun
Keywords: Technologie; stavba; zdivo; výztuž; bednění; beton; příhradový vazník; valník; autodomíchávač; autojeřáb; technologický předpis; bezpečnost práce; zařízení staveniště; časový plán; rozpočet.; Technology; construction; masonry; framework; formwork; monolit; truss tie; flatbed; concrete mixer; mobile crane; technological instruction; work safety; building equipment; scheduling; budget of the building.